1998
DOI: 10.1038/sj.leu.2400978
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical heterogeneity of CD4+CD8+ double-positive chronic T lymphoid leukemia

Abstract: Chronic T lymphoid leukemias are defined as leukemias of post-thymic T cells. The CD4 ؉ CD8 ؉ double-positive (DP) phenotype is seen in a few cases. Since DP generally occurs in thymic T cells, whether the DP T leukemia cells represent thymic or peripheral T cells has been a matter of controversy. To address this issue, we studied phenotypical features in eight cases of DP T cell leukemia. Thymic DP T cells and peripheral CD8 ؉ T cells have CD8 of ␣␤ subunit, while CD8␣␣ is induced in CD4 ؉ T cells on activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
(25 reference statements)
2
18
0
Order By: Relevance
“…Demonstration of in vivo infection of these cells highlights the role that they may play in HIV-mediated dysregulation in the CD8 ϩ T-cell compartment. 26 Double-positive (CD4 ϩ CD8 ϩ ) T cells have been reported in a number of clinical conditions such as HTLV-1 infection, 29 chronic T-lymphoid leukemia, 35 Sjögren syndrome, 36 myasthenia gravis, [17][18][19]37 multiple sclerosis, 38 idiopathic thrombocytopenic purpura, 39 and Behçet syndrome. 40 These cells may play a role not only in HIV pathogenesis but also may constitute a normal response to CD8 ϩ T-cell activation and, hence, may also play a role in normal T-cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of in vivo infection of these cells highlights the role that they may play in HIV-mediated dysregulation in the CD8 ϩ T-cell compartment. 26 Double-positive (CD4 ϩ CD8 ϩ ) T cells have been reported in a number of clinical conditions such as HTLV-1 infection, 29 chronic T-lymphoid leukemia, 35 Sjögren syndrome, 36 myasthenia gravis, [17][18][19]37 multiple sclerosis, 38 idiopathic thrombocytopenic purpura, 39 and Behçet syndrome. 40 These cells may play a role not only in HIV pathogenesis but also may constitute a normal response to CD8 ϩ T-cell activation and, hence, may also play a role in normal T-cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported the presence of circulating blood DP T cells, in both healthy [13,14] and diseased individuals [15][16][17][18][19][20][21][22]. Existence of this unconventional and rare lymphocyte population in peripheral blood has been hypothesized to result from premature release of immature CD4 + CD8 + T cells from the thymus to the periphery, where their maturation into functionally competent SP cell continues [23].…”
Section: Introductionmentioning
confidence: 99%
“…32 ATM mutations cDNA or DNA samples were screened using PTT or SSCP followed by DNA sequencing to identify the mutations. Germline mutations in the A-T gene were found in all A-T patients (Table III).…”
Section: Immunophenotypingmentioning
confidence: 99%